Immigration History, Entry Jobs, and the Labor Market Integration of Immigrants - Laura Ansala; Olof Åslund; Matti Sarvimäki (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2020)
This paper studies the relationship between past immigration experiences of the host country and the way new immigrants enter the labor market. We focus on two countries - Finland and Sweden - that have similar formal institutions but starkly different immigration histories. In both countries, immigrants tend to find their first jobs in low-paying establishments, where the manager and colleagues share their ethnic background. The associations between background characteristics, time to first job, other entry job characteristics, earnings dynamics and job stability are also remarkably similar. These results are consistent with the hypothesis that the host country's immigration history plays a limited role in shaping the integration process.
Keywords: 330